A 0.6 V 31 nW 25 ppm/°C MOSFET-only sub-threshold voltage reference. (August 2017) - liang, Yuhua; Zhu, Zhangming
Abstract: A low-power low-supply high-LR high-PSR MOSFET-only voltage reference is proposed in this paper. The proposed voltage reference is designed in the standard 0.18 µm CMOS process. In the typical case, when the temperature sweeps from −20 °C to 80 °C, the simulation result shows that the proposed voltage reference achieves a temperature coefficient of 25 ppm/°C. And the line regulation is as high as 0.067%/V, at room temperature. At the low frequency (<100 Hz), a PSR of 44 dB is obtained. The reference succeeds in working at the supply voltage as low as 0.6 V, with the power consumption being 31nW. The proposed voltage reference occupies an area of 130 µm × 55 µm.